A Secondary Abdominal Pregnancy Threat to Maternal Life - Ashraf, Fatema; Choudhury, Farzana Rabee; Yesmin, Nilufar; Islam, Zinnat Ara; Yusuf, Md. Abdullah (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll, 2011; 3 (1): 24-26 DOI: http://dx.doi.org/10.3329/jssmc.v3i1.12057